The positive impact of dental care on the patient's quality of life after cancer treatment: a case report (Research, Society and Development, 2020)
Objective: To report the case of a patient after cancer treatment and evaluate the impact of oral health on quality of life, through the Oral Health Impact Profile (OHIP-14) before, during, and after dental treatment. Methodology: A patient after antineoplastic treatment attended the clinic specialized. In all consultations, OHIP-14 was applied. Case report: A 68-year-old man diagnosed with keratinizing squamous cell carcinoma of the larynx (T3N0MX), undergoing chemotherapy and adjuvant radiotherapy (2878.2 Grays) and vertical partial laryngectomy surgery without ganglionic emptying. After CT, he complained of tooth loss and discomfort in the tongue after radiotherapy. Ex-drinker for 5 years, ex-smoker for 6 months, but alcoholic for> 10 years and smoker